Study on the Influence Law of CO₂ Treatment on Emulsion Stability - Lu, Peiyu; Jiang, Shuxuan (Scientific Journal of Technology, 2026)
The formation of water-in-oil (W/O) emulsions during crude oil extraction leads to increased pipeline load, higher energy consumption, and elevated demulsification costs. CO₂ flooding technology can significantly improve emulsion stability by altering oil/water interfacial properties. This study investigates the influence law of CO₂ on the stability of W/O emulsions through experimental and theoretical analyses. Using a pressurized emulsification device and a high-speed microscopic observation system, combined with the water separation rate method and micromorphological analysis, the demulsification mechanism of CO₂ was revealed. Experimental results show that as the CO₂ pressure increases from atmospheric pressure to 2 MPa, the demulsification rate increases and the interfacial tension decreases. High-speed microscopic observations indicate that the droplet coalescence process can be divided into four stages: contact, deformation, film rupture, and coalescence. A mathematical stability model incorporating a deformation coefficient, contact angle correction, and pressure coefficient was established. CO₂ destabilizes emulsions through a dual mechanism: reducing the oil-phase viscosity and weakening the interfacial film strength. This study provides an important theoretical basis for optimizing CO₂ flooding technology.